2018
DOI: 10.1111/eea.12699
|View full text |Cite
|
Sign up to set email alerts
|

Optimal pheromone trap density for mass trapping cacao mirids

Abstract: Sahlbergella singularis Haglund and Distantiella theobroma (Distant) (Heteroptera: Miridae) are the key insect pests of cacao in Ghana and elsewhere in West Africa. Since 1954, spraying with synthetic insecticides has been the principal means of controlling these pests. In West Africa, environmental concerns, economic stimuli, and unreliable access to insecticides have stimulated interest in ecologically more benign mirid control strategies as an alternative to a total reliance on insecticides. Males of both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…Only four Distantiella theobroma were trapped in this study. The low numbers here and in our previous studies at Akwadum (Sarfo et al, 2018a) and Acherensua (Sarfo et al, 2018b), probably reflects a fall in its abundance in Ghana first suggested by Owusu-Manu (2002) and since confirmed from an analysis of 34 years monitoring data of mirids from the Eastern Region of Ghana by Adu-Acheampong et al (2017).…”
Section: Discussionsupporting
confidence: 78%
“…Only four Distantiella theobroma were trapped in this study. The low numbers here and in our previous studies at Akwadum (Sarfo et al, 2018a) and Acherensua (Sarfo et al, 2018b), probably reflects a fall in its abundance in Ghana first suggested by Owusu-Manu (2002) and since confirmed from an analysis of 34 years monitoring data of mirids from the Eastern Region of Ghana by Adu-Acheampong et al (2017).…”
Section: Discussionsupporting
confidence: 78%
“…Pheromone‐based traps, aerosol dispensers or pheromone lures can occasionally be used for mass‐trapping or mating disruption, thus contributing to a varying extent to pest control in certain crop × pest systems 41‐43 . Pheromone trap captures—at a limited number of field sites—were in accordance with field‐level L. pratensis abundance, with capture rates lower in insecticide‐treated cotton fields (< 25 males per week) (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Traps baited with pheromone lures will be helpful in early detection of pest, mating disruption and timing of management procedures based on threshold 10 . Mass trapping of cocoa mirids has been efficiently done by pheromone trapping 11 .…”
Section: Quick Response Codementioning
confidence: 99%